DEVELOPMENT OF cREATIVE COMPETENCE OF EDUCATORS IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Raxmatova Ikbolxon Inomjonovna; Choriyeva Zebiniso Rustam qizi (Journal of new century innovations, 2023)
Abstract: This article is about the creativity of educators in preschools qualities,improvement of methods of developing creative competence theoretical foundations are highlighted.